Co teologia ma do powiedzenia ekonomii? Kilka uwag teologiczno-moralnych na temat życia gospodarczego - Kacprzak, ks. Jacek (Annales. Etyka w Życiu Gospodarczym, 2015)
Is theology able to communicate anything to the economy at all? Would not it bean invasion to an autonomous field of knowledge capable to organize economicactivity of man according to its internal rules? However, when asking the economicquestion of how to satisfy material needs, one cannot ultimately avoid anotherquestion – an ethical one – of what the purpose of satisfying those needs is. Whatis man really looking for? Theology, on the plane of faith and reason, tries to findanswers to these fundamental, ultimate questions asked by human beings, who arenowadays often tired of searching for happiness in satisfying the short-term andoften artificially created new and new needs. A theologian in his research listensfirst of all to the word that God pronounces to man. This word, contained in theBible, sets out the basic lines of the dignity of man, his tasks and the ultimate goalof his existence, which is to achieve full humanity and maturity, namely happinessin God. Only in such a perspective, which goes beyond the mundane, one canproperly evaluate every action of man, giving it a rightful place in the whole of hisexistence. Specific issues relating to man’s economic activity, as described in theBible, invariably refer to this overall dimension of his existence and his ultimatefulfilment in God as the guarantor of order and the source of life. Hence, any humanactivity which ignores the structure of that order, planned by the Creator,appears to be disordered and, consequently, leads to the destruction of man himself.